Preparation and Characterization of CdO Thin Films Obtained by Oxidation of Obliquely Evaporated Cd Thin Films - Khalef, Wafaa K (Al-Nahrain Journal of Science, 2018)
In this work, oblique angle deposition technique (OAD) was used to grow cadmium thin films onto glass substrates at different angles (0º and 70º), and then oxidized in air at (500 °C) for 1 hour by conventional furnace as the oxidation source. The effect of deposition angle on the structural, morphology, optical and electrical properties of cadmium oxide thin film were studied. XRD technique used to study the crystalline structure of these films confirm the polycrystalline nature of these films and the higher intensity accompanied that deposited with (70˚) with preferred orientation (111). Some structural parameters such as grain size was calculated. The surface morphology shows an improvement with higher incident angle. The optical properties shows that the transmition decreasing with increases deposition angle and the optical energy gap (Eg) values are (2.4 and 2.8) eV for normal and oblique deposition respectively. The dark current increases linearity with applied voltage and deceases with increasing deposition angle at the fixed applied voltage (ohmic behavior) with activation energy found to be (0.1544 - 0.3323) ( eV) for normal and oblique deposition respectively .